Detection of turkey astrovirus in young poults affected with poult enteritis complex in Brazil - Da Silva, Sergio E. L. (2008)
Reverse transcription polymerase chain reaction (RT-PCR) of turkey astrovirus (TAstV) capsid and polymerase genes was applied to the bursa of Fabricius (BF), thymus (TH), spleen (SP) and cloacal swabs (CS) of young poults with "Poult enteritis complex" (PEC). The histological lesions included atrophy, lymphoid depletion, cellular infiltration and necrosis of the BF, TH and SP, respectively. The RT-PCR reactions were positive for the polymerase gene of TAstV-2 in all 100 CSs, 7 out of 10 of BFs and 10 out of 20 THs and SPs, respectively. Five out of 10 THs and SPs samples, considered to be negative by RT-PCR, were positive when specific primers designed for the TAstV-2 capsid gene were applied. This is the first description of turkey astrovirus infection presenting PEC in Latin America.